Banjarese Scholars and the Evolution of Islamic Education in South Kalimantan Circa 1900-1950 - Rahmadi, Rahmadi; Jamalie, Zulfa; Yaqin, Husnul (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
This article provides a historical overview of Banjarese scholars who were alumni of the Middle East and Islamic organizations in South Kalimantan, as well as their roles in the development of Islamic educational institutions in the early 20th century. The research employs historical methods with a social-intellectual history approach. The study reveals a significant increase in the number of Middle Eastern alumni in early 20th-century South Kalimantan. These scholars studied in Haramain and Egypt (al-Azhar) during that period. Concurrently, with the rise in the number of Middle Eastern alumni, various Islamic organizations emerged, both locally and nationally. These organizations included Sarekat Islam, Muhammadiyah, Nahdlatul Ulama (NU), and Musyawaratuththalibin (MTH). Both Middle Eastern alumni and these Islamic organizations collaborated and contributed to establishing Islamic educational institutions, particularly madrasahs, in various regions. They successfully transformed traditional educational systems of majelis taklim (study circles or religious study gatherings) and langgar barangkap (a two-story small mosque) into madrasahs. Some of these madrasahs served as precursors to institutions that later evolved into Islamic boarding schools in the second half of the 20th century. The traditional education system underwent a shift towards a more modern approach, incorporating classical education and general knowledge into the madrasah curriculum. They also established madrasah associations to coordinate and standardize madrasah education systems. Furthermore, they initiated the establishment of Islamic higher education institutions, although this was not fully realized in the early 20th century.